THE Identification Pending Claim of Healthcare and Social Security Agency Insurance at Nirmala Suri Hospital. - Linda Widyaningrum; Warsi Maryati; Rizki Nurul Wulandari (LPPM Universitas Duta Bangsa Surakarta, 2022)
A pending claim is a claim that is returned by the BPJS (Social Security Administering Agency) Health verifier to the hospital for revision which can later be resubmitted. This study aims to determine the causes of pending BPJS claims for inpatients at Nirmala Suri Sukoharjo Hospital in 2020. This study is a descriptive study, with a retrospective approach. Samples of 685 claims are pending with the saturated sample technique. The research instrument was in the form of observation guidelines and interview guidelines. Data processing with classification, editing, and presentation of data in text form. Data processing with data analysis is done descriptively. The implementation of BPJS patient claims at the Nirmala Suri Sukoharjo Hospital has been implemented and has implemented the existing SPO (Standard Operating Procedures). There are 14 classifications of pending BPJS claims for inpatients at Nirmala Suri Sukoharjo Hospital. The causes of pending BPJS claims for inpatients at the Nirmala Suri Sukoharjo Hospital in 2020 include: completeness of medical record documents, clarity of doctor's writing, and application system updates. Coordinate with related units such as medical records and registration units, inpatient installations, emergency units, cashier units, and pharmacy installations regarding matters that affect pending claims so that they do not happen again. It is better if the coder requires updating the latest knowledge and rules related to coding rules or BPJS Health rules and it takes the accuracy of the coder and grouper in the coding and input process